Intelligent distributed computing IX : proceedings of the 9th International Symposium on Intelligent Distributed Computing - IDC'2015, Guimarães, Portugal, October 2015 /: proceedings of the 9th International Symposium on Intelligent Distributed Computing - IDC'2015, Guimarães, Portugal, October 2015. (2015) - Unknown
No abstract available